Emojis as Pictures - Emar Maier (Ergo, An Open Access Journal of Philosophy)
I argue that emojis are essentially little pictures, rather than words, gestures, expressives, or diagrams. 🎁 means that the world looks like that, from some viewpoint. I flesh out a pictorial semantics in terms of geometric projection with abstraction and stylization. Since such a semantics delivers only very minimal contents I add an account of pragmatic enrichment, driven by coherence and non-literal interpretation. The apparent semantic distinction between emojis depicting entities (like 🚗) and those depicting facial expressions (like 😊) I analyze as a difference between truth-conditional and use-conditional pictorial content: 🚗 depicts what the world of evaluation looks like, while 😊 depicts what the utterance context looks like.